2002
DOI: 10.1101/gad.1007902
|View full text |Cite
|
Sign up to set email alerts
|

Cancer predisposition and hematopoietic failure in Rad50S/S mice

Abstract: Mre11, Rad50, and Nbs1 function in a protein complex that is central to the metabolism of chromosome breaks. Null mutants of each are inviable. We demonstrate here that hypomorphic Rad50 mutant mice (Rad50 S/S mice) exhibited growth defects and cancer predisposition. Rad50 S/S mice died with complete bone marrow depletion as a result of progressive hematopoietic stem cell failure. Similar attrition occurred in spermatogenic cells. In both contexts, attrition was substantially mitigated by p53 deficiency, where… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
182
1

Year Published

2003
2003
2014
2014

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 187 publications
(193 citation statements)
references
References 75 publications
(85 reference statements)
10
182
1
Order By: Relevance
“…The Rad50 +/46 phenotype is ATM-dependent Precedent for the hypothesis that Rad50 +/46 phenotypes could be ATM-dependent comes from Rad50 S/S mice, which at both the cellular and organismal levels exhibited phenotypes reminiscent of Rad50 +/46 (Bender et al 2002;Morales et al 2005). We found that most aspects of the Rad50 +/46 pathology, including hydrocephalus ( Fig.…”
Section: Dna Repair and Checkpoint Signaling In Rad50 +/46 Cellsmentioning
confidence: 65%
See 1 more Smart Citation
“…The Rad50 +/46 phenotype is ATM-dependent Precedent for the hypothesis that Rad50 +/46 phenotypes could be ATM-dependent comes from Rad50 S/S mice, which at both the cellular and organismal levels exhibited phenotypes reminiscent of Rad50 +/46 (Bender et al 2002;Morales et al 2005). We found that most aspects of the Rad50 +/46 pathology, including hydrocephalus ( Fig.…”
Section: Dna Repair and Checkpoint Signaling In Rad50 +/46 Cellsmentioning
confidence: 65%
“…MEFs and EFs were generated, cultured, and immortalized as described (Bender et al 2002). Rad50 +/47 EFs were generated from Rad50 +/Neo47 chimeric mice by growing the cells in medium containing 1 mg/mL G418 followed by lentiviral delivery of Cre and clonal selection.…”
Section: Cellular Assaysmentioning
confidence: 99%
“…Similarly, mice carrying a mutation in either Rad50 or Rad51 show increased apoptosis. 11,12 Moreover, it has recently been reported that inactivation of the p53 inhibitor iASPP, and its worm counterpart ape-1, induces apoptosis in a p53-dependent manner. 13 We independently identified ape-1 in our RNAi screen, and confirmed that its inactivation requires p53 to cause a Gla phenotype (Table 1 and see below).…”
Section: Resultsmentioning
confidence: 99%
“…Thus, the Rad50K22M allele (equivalent to yeast R20M) was studied (Figure 1). The FRad50S_ mice showed not much meiotic phenotype, and were fertile: although there was a cellular attrition in testes, there was no meiotic recombination defect, normal meiotic progression and chromosome morphology (Bender et al 2002). Amazingly, these mice showed almost no cellular phenotype, unlike the other Mre11 complex hypomorphic mutations: cells were not sensitive to DNA damage and showed no radioresistant DNA synthesis (RDS).…”
Section: Animal Models For Mutations In the Mre11 Complexmentioning
confidence: 96%
“…Amazingly, these mice showed almost no cellular phenotype, unlike the other Mre11 complex hypomorphic mutations: cells were not sensitive to DNA damage and showed no radioresistant DNA synthesis (RDS). There were wild-type levels of protein, but a profound impact on the organismal level (Bender et al 2002). In these mutants there is a constitutive damage (increase of chromosome breakage and constitutive histone H2AX phosphorylation) (Bender et al 2002) and a constitutive activation of PIPK3 kinases, probably due to unprocessed Fphysiological_ damage (Bender et al 2002, Morales et al 2005).…”
Section: Animal Models For Mutations In the Mre11 Complexmentioning
confidence: 99%